Determinants of a political party's social media strategy: A comparative analysis of Tanzania's opposition political parties' Twitter practices. (March 2022) - Kwayu, Aikande Clement
The impact of political context on a political party's organizing and mobilizing strategies has been noted in the literature. Opposition political parties operating in autocratic contexts look for different ways in which they can communicate, organize, and mobilize their members. Advances in digital technology and, in particular social media, have created such spaces in which political parties can communicate and mobilize their members. In Tanzania, the state has imposed repressive political restrictions against opposition parties. In this context, it would be assumed that opposition political parties would turn to social media as an alternative means for mobilization and communication due to restrictions in traditional spaces such as mainstream media and rallies. This article argues that, in Tanzania, the opposition political parties' levels of institutionalization and resources determine their use of social media more than the repressive political context. The study compares the Twitter use of two opposition parties—Chadema and ACT-Wazalendo—in two periods between 2016 and 2020, which is the period of increasing authoritarian tendencies in the country. The study deploys a qualitative research methodology using a case study approach and collection of data from the parties' practices in their official Twitter accounts as well as key informant interviews.